The Impact of a Conducive Work Environment and Salary Welfare on the Performance of PAUD Teachers - Purbiyanto, Eko; Santosa, Tri Budi; Panjtarani, Ari (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the influence of a conducive work environment and salary welfare on the performance of Early Childhood Education (PAUD) teachers in Banjarsari District, Surakarta City. The performance of PAUD teachers is an important factor in the quality of education which is influenced by various factors, including working environment conditions and financial well-being. The research method used is a quantitative survey with a descriptive approach. Data was collected through questionnaires distributed to PAUD teachers in the area, and analyzed using regression analysis to measure the influence of the work environment and salary welfare on teacher performance. The research results show that a conducive work environment has a significant positive effect on teacher performance, as well as salary welfare. The combination of these two factors shows a strong relationship in increasing the motivation and work effectiveness of PAUD teachers with an R2 value of 55.9%, the remaining 41% was not examined in this research. These findings provide practical implications for school administrators and policy makers to create a better work environment and increase salary welfare in order to improve the performance of PAUD teachers, which in the end can have a positive impact on the quality of early childhood education.